Importância dos efeitos de absorção no espalhamento elástico de elétrons por moléculas - Ferraz, Jorge Ronan (2017)
In this work we study the importance of absorption effects on the electron-molecule interaction dynamics. These effects are simulated by a complex optical model potential from which the imaginary part is an absorption potential. In the numerical solution of the scattering electron wave equation, Padé’s approximant technique is used in association with the partial-wave expansion method. In our calculations, the scattering wave function, the interaction potential and all the related matrices are single-center expanded about the center of mass of the molecule, in terms of the angular symmetry-adapted functions xpM. The well-known convergence difficulty for polar targets is overcome in our studies by the use of a closure technique based on the First Born Approximation. We carry out studies on electron scattering by eight molecules: ammonia, formaldehyde, fluoromethane, formamide, dimethyl ether, dimethyl sulfide, pyrimidine, and acetone, all of them featuring a strong permanent electric dipole. We report elastic electron-molecule scattering differential (DCS), integral (ICS) and momentum transfer (MTCS) cross sections, as well as electron-molecule scattering total (TCS) and total absorption (TACS) cross sections for all the above-mentioned molecules. Our theoretical results are compared to experimental and other theoretical data available in the literature. Our results show the importance of absorption effects on electron-molecule scattering for incident electron energies in the (20-500) eV range.